Analisis Manajemen Konflik dan Stres Kerja Pengaruhnya Terhadap Kinerja Karyawan pada PT XYZ di Kota Batam - Bipianto, Iwan; Wasiman, Wasiman (Prosiding, 2024)
This study aims to examine the impact of conflict and work stress on employee performance at PT XYZ in Batam City. The results indicate that work conflict does not significantly affect employee performance, as evidenced by a correlation coefficient of only 0.001. The t-test results show that H0 cannot be rejected with a t-value of -0.005 < t-table value of 2.042. On the other hand, work stress has a significant effect on employee performance with a correlation coefficient of 0.459, indicating a 21.06% impact of work stress on performance. However, when considered together, conflict and work stress have a significant combined effect on employee performance with a correlation coefficient of 0.647, accounting for 41.86% of the influence on performance. The remaining 58.14% is affected by factors not included in this study